Revitalizing the Roles of Higher Education in the Preservation of Harmony among Religious Society - Muhaemin Muhaemin (State Islamic Institute of Palopo, 2023)
Inter-Religious harmony is a strong foundation in the context of a pluralistic society. To treat harmony, the role of various elements of society, including universities, is needed. This paper focuses on the role of universities in the development of religious harmony through the mission of teaching education, research and community service. This study uses a qualitative approach with the subject of research is the leader and lecturer of the State Islamic Higher Education in Eastern Indonesia. The results of the study indicate that the State Islamic College of Sorong West Papua has conducted many dialogues with interfaith leaders. The Dato Karama Palu State Islamic Religion Institute provided extensive opportunities for lecturers in the activities of harmony formation including the formation of former terrorist prisoners. Makassar Alauddin State Islamic University facilitates interfaith studies with various Theological Colleges in Makassar. The inter-religious harmony is very influential in the life of the state to realize the Indonesian nation that is highly competitive in the international arena. The presence of Islamic Higher Education can provide a solution to anticipate the emergence of new social conflicts in various regions in Indonesia. This study recommends the need for synergies between universities in optimizing the role of universities in harmonizing harmony among religious groups.